A közlekedési-telekommunikációs viszonyok hatása a városok szerkezetének alakulására - Erdősi, Ferenc (Tér és Társadalom, 1990)
The utilization of individual regions and the possibility of a differentiated use of settlements depend, on the one hand, to a great extent on their accessibility. On the other hand, the settlement-specific characters of a given society and economy condition the transport and communication system. The present study concentrate on the first aspect of the above mentioned interaction. First we seek answers to questions concerning the role of different transportation–communication technologies (together with other infrastructural conditions) in the historical transformation of the internal structures of cities and towns. Then we outline the new possibilities provided by new information–communication technique in the conscious restructuring of urban space, creating the ’information city’. The extensive use of telematic opens up a new age in the transformation of urban structure, namely: worlcing places move into homes. In the information society the historically established spatial relations of working and dwelling places change strikingly. Qualitative demands for homes and dwelling environment become stronger, and at the same time city centres partly have loose their central–administrative functions. Residential districts obtain a mixed function. They are working and dwelling place at the same time. In the establishment of new working places the role of physical distance and accessibility has been declining. At the same time other factors like amenities of dwelling environment and conditions of leisure activities play more and more important role. Suburbanisation process is accelerating and city functions are restructuring. Service and cultural functions of cities are becoming decisive. In the most developed countries the information sector is viewed as conscious means of settlement development. New information technologies can play important role in restructuring declining regions, through establishing ’communication cities’ or telematic ports (Kawasaki, Osaka , Yokohama and London’s dockyards). The revival of towns in peripheric, underdeveloped regions can be achieved be means of new information technologies which connect them to world-scale information networks.